TEACHING WRITING RECOUNT TEXT BY USING TEXT TO SELF CONNECTION TECHNIQUE - Pratama, Reza; Sutapa, Y Gatot; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The aim of this research was to figure out whether or not text to self-connection technique was effective in teaching recount text writing to the year eight students of SMPN 3 Pontianak in academic 2017/2018. Text-to-self connection technique was used to teach recount text writing by connecting the reading text and students’ experiences. The form of the research was pre-experimental study with one group pre-test post-test design. The population of this research was the eighth grade students with the total number of students were 341. The sample of this research was VIII A which consisted of 35 students. Through writing test in form of writing an essay, it was found that the students writing achievementincreased positively. It was proven by the learning outcomes of the students’ writing after being accustomed to writing using text to self-connection technique.Text to self-connection technique enabled the students how to elaborate and construct the ideas better for writing. Furthermore, it assisted the students how to construct the sentence and organize the generic structures. It was concluded that text to self-connection technique was effective and had a strong effect in writing recount text. Therefore, text-to-self connection technique is highly recommended for teaching recount text writing.Keywords: Text to Self-connection technique, Teaching Writing, Recount Text